Meningkatkan Pemahaman tentang Kewirausahaan di Kalangan Lembaga Lansia Indonesia - Sarah Sentika; Rivaldi Arissaputra; Maisa Azizah Asmara (Politeknik Piksi Ganesha Indonesia, 2026)
This community service program aimed to improve entrepreneurial understanding among members of the Indonesian Elderly Association (LLI) in Lengkong District, Bandung City. The participants consisted of 28 active elderly members of LLI. The main problems identified were the limited understanding of entrepreneurial concepts, the benefits of entrepreneurship in later life, methods for identifying business ideas, steps to start a business, and strategies to overcome digital technology challenges. The program was implemented using a participatory training method with an andragogical approach through interactive lectures, group discussions, hands-on practice, and question-and-answer sessions. Evaluation was conducted using a pre-test and post-test design on five indicators measured with a 1–5 Likert scale. The results demonstrated significant improvements across all indicators. The average understanding score increased from 2.19 before the training to 4.38 after the training. The program proved effective in enhancing entrepreneurial understanding among the elderly and is recommended for replication in other regions with similar characteristics